Dual Semantics of the Latin inter(-) - Filimonov, Evgeniy (Philologia Classica, 2019)
The paper analyzes the function of the prefix inter-, which allows to reduce the 15 main senses (described in the OLD) to the basic two. The sense of the prefix depends on the situation described with the compound: a) the situation of dividing space: ‘a border between two or more points disconnecting them’ (inter hostes flumen erat). Most of the verbs in this group are transitive and accompanied by a countable object: intercalare ‘to insert a day or month into the calendar’; interloqui ‘to interrupt, to speak between’. b) the situation of connected space: ‘all the space (or time) between two points connecting them within the same situation’ (inter arma tacent musae). The majority of these verbs are transitive and are used with an uncountable object: interbibere ‘to drink dry, drain’; interlegere ‘to pick off here and there, to thin’. Some verbs can have either sense depending on the context (interesse: a. ‘to lie between, intervene’ modo inter me atque te murus intersit (Cic. Cat. 1. 10.), b. ‘to be in the company of, to take part’ legit scripta de se carmina, legit historias, et posteritati suae interfuit (Plin. Ep. 2.1.2). On the basis of this classification principle four verbs are analyzed in which the meaning of the prefix inter- is unclear: interire, interficere, interimere, intellegere. Three of them have the prefix inter– in the sense of division and form pairs of compounds (an intransitive verb of state interire — a verb of action interimere, interficere). The verb intellegere has two senses as different stages of its semantic development: 1. ‘to choose between’, ‘to notice, discern’ and 2. ‘to collect together (all the parts)’ > ‘to grasp, understand (the whole picture of an object or a situation)’.